1999
DOI: 10.1093/oxfordjournals.schbul.a033370
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuropsychophysiological Asymmetry in Schizophrenia: A Review and Reorientation

Abstract: In reviewing the neuropsychophysiological evidence of functional asymmetry it is proposed that schizophrenia is characterized by a greater dispersion of leftward and rightward asymmetries. The two extremes are represented by active (left greater than right) and withdrawn (right greater than left) syndromes, as is the case with psychometric schizotypy. Syndrome-asymmetry relations extended beyond fronto-temporal systems to include posterior activity, infracortical motoneuron excitability, and individual differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 225 publications
(309 reference statements)
7
68
0
1
Order By: Relevance
“…Our findings of CC anisotropy abnormalities are also consistent with other findings in the literature (Agartz et al, 2001;Foong et al, 2001;Ardekani et al, 2003). Moreover, Gruzelier (1999) speculates that information processing deficits in schizophrenia are related to defective interhemispheric communication, mediated by the CC. Another speculation is that, because of the long maturation period for CC myelination, an insult to the developing brain may contribute to a decrease in connectivity between the right and left hemispheres (Njiokiktjien, 1988) and thus might explain the lack of asymmetry between the hemispheres observed in schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings of CC anisotropy abnormalities are also consistent with other findings in the literature (Agartz et al, 2001;Foong et al, 2001;Ardekani et al, 2003). Moreover, Gruzelier (1999) speculates that information processing deficits in schizophrenia are related to defective interhemispheric communication, mediated by the CC. Another speculation is that, because of the long maturation period for CC myelination, an insult to the developing brain may contribute to a decrease in connectivity between the right and left hemispheres (Njiokiktjien, 1988) and thus might explain the lack of asymmetry between the hemispheres observed in schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
“…In schizophrenia, dopamine is known to be implicated in functional neuropsychophysiological asymmetry (for a review see [86]). McGowan and colleagues [20] as well as Hietala and co-workers [21] reported that abnormal presynaptic dopamine density (measured by 6-[18F]-fluorodopa uptake) was lateralised to the left in patients with schizophrenia.…”
Section: Lateralisation Of Dopamine Abnormalitiesmentioning
confidence: 99%
“…[134][135][136] Neuroanatomical studies have found differences between schizophrenia patients and controls in the number, density or distribution of neurons between the left and right hemispheres. 8,137,138 Abnormalities of laterality have also been revealed by brain imaging studies measuring subregional tissue volume, blood flow, and metabolism.…”
Section: Anomalous Cerebral Lateralizationmentioning
confidence: 99%
“…There is an unclear relationship between these structural abnormalities, and the behavioral asymmetries in schizophrenia which are purportedly manifested in motor, sensory, language and cognitive function. 134,135 The idea that these lateralization abnormalities arise during development is gaining support, but little attention has been given to the possible involvement of a viral infection.…”
Section: Anomalous Cerebral Lateralizationmentioning
confidence: 99%